1994
DOI: 10.1161/01.cir.89.5.2015
|View full text |Cite
|
Sign up to set email alerts
|

Continuing evolution of therapy for coronary artery disease. Initial results from the era of coronary angioplasty.

Abstract: BACKGROUND Survival after coronary artery bypass graft surgery (CABG) and medical therapy in patients with coronary artery disease (CAD) has been studied in both randomized trials and observational treatment comparisons. Over the past decade, the use of coronary angioplasty (PTCA) has increased dramatically, without guidance from either randomized trials or prospective observational comparisons. The purpose of this study was to describe the survival experience of a large prospective cohort of CAD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
180
0
10

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 381 publications
(202 citation statements)
references
References 40 publications
9
180
0
10
Order By: Relevance
“…Percutaneous or surgical revascularization after the acute event is associated with an early hazard, followed by a reduced risk of death over the later period. Studies of elective bypass surgery, 21,22 angioplasty, 23 and revascularization after MI 24 all show this pattern. Thus, the lower mortality rates of survivors of the acute phase should not be taken as definitive evidence that revascularization prolongs survival (also keeping in mind the possibility of selection of a less-sick subgroup), just as the increased mortality rates in the first few days after revascularization should not be taken to indicate that revascularization increases mortality rates overall.…”
Section: Revascularizationmentioning
confidence: 90%
“…Percutaneous or surgical revascularization after the acute event is associated with an early hazard, followed by a reduced risk of death over the later period. Studies of elective bypass surgery, 21,22 angioplasty, 23 and revascularization after MI 24 all show this pattern. Thus, the lower mortality rates of survivors of the acute phase should not be taken as definitive evidence that revascularization prolongs survival (also keeping in mind the possibility of selection of a less-sick subgroup), just as the increased mortality rates in the first few days after revascularization should not be taken to indicate that revascularization increases mortality rates overall.…”
Section: Revascularizationmentioning
confidence: 90%
“…those with medium-severity CAD) become more likely to receive PTCA relative to CABG over time. Modifying an index from Mark et al (1994), we divide patients into three severity categories: low, medium, and high. 8 This categorization provides a rough control for the effects of any changes over time in the average severity of the population receiving revascularization.…”
Section: Data and Descriptive Analysismentioning
confidence: 99%
“…This patient population is one of the most controversial, from an outcome perspective. Early registry studies comparing PTCA and CABG showed a trend toward improved survival following surgical revascularization in this patient population (17)(18)(19)(20)(21). However, RCTs from the PCI era, which used stents and GP IIb/IIIa inhibitors, are conflicting.…”
Section: Pci Versus Cabgmentioning
confidence: 99%
“…Several registry studies comparing balloon angioplasty (percutaneous transluminal coronary angioplasty [PTCA]) and CABG showed a trend toward improved survival following surgical revascularization in this patient population (18)(19)(20)(21). However, RCTs from the PCI era, which used stents and glycoprotein (GP) IIb/IIIa inhibitors, are conflicting.…”
Section: Ou Pontage Aortocoronarien [Pac])mentioning
confidence: 99%